The region of the Strandja Sill (North Turkey) and the Messinian events. (September 2015) - Suc, Jean-Pierre; Gillet, Hervé; Çağatay, M. Namik; Popescu, Speranta-Maria; Lericolais, Gilles; Armijo, Rolando; Melinte-Dobrinescu, Mihaela Carmen; Şen, Şevket; Clauzon, Georges; Sakınç, Mehmet; Zabcı, Cengiz; Ucarkus, Gülsen; et al.
Abstract: The two sides of the Strandja Sill show a highly discontinuous stratigraphic succession since the Late Oligocene. This area, together with the Sea of Marmara Basin, is usually proposed as the gateway for the Paratethyan freshwaters and organisms that constituted the Lago Mare facies in the Mediterranean Sea during the Messinian Salinity Crisis (MSC). Our investigations involving new field observations and datings, together with previous studies, suggest that the sill has possibly experienced such a connection at around 8 Ma, i.e. significantly before the crisis. The proposal of a sea-level drop of the Black Sea before 7 Ma is not supported by our data on dinoflagellate cysts. Consistency of calcareous nannofossil succession at DSDP Site 380 is reinforced, allowing to reassert that subaerial erosion impacted both the southwestern Black Sea and the central Marmara – Dardanelles area during the peak of the MSC. At that time, this region was crossed by two oppositely directed fluvial networks, further supporting the absence of a marine gateway through the Strandja Sill. It is concluded that none of the Lago Mare events recorded in the Mediterranean during the MSC were the consequence of the passage of Paratethyan waters and organisms through this area. In the Black Sea, the well-dated Messinian fluvial erosion can be followed offshore. The overlying prograding deltaic deposits attest to a fast marine reflooding after the crisis. This constitutes a comprehensive erosion – sedimentation model in an area intensively explored for hydrocarbons. Highlights: Two opposite fluvial networks crossed the Thrace Basin between 6 and 5 Ma. Evidence of subaerial erosion in the Black Sea at that time is reinforced. Paratethys–Mediterranean did not connect over the Strandja Sill at that time. A Balkans corridor was used by Paratethyan organisms for the Lago Mare facies.